2015
DOI: 10.4103/0975-1475.172451
|View full text |Cite
|
Sign up to set email alerts
|

3D evaluation of palatal rugae for human identification using digital study models

Abstract: Background:While there is literature suggesting that the palatal rugae could be used for human identification, most of these studies use two-dimensional (2D) approach.Aim:The aims of this study were to evaluate palatal ruga patterns using three-dimensional (3D) digital models; compare the most clinically relevant digital model conversion techniques for identification of the palatal rugae; develop a protocol for overlay registration; determine changes in palatal ruga individual patterns through time; and invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 26 publications
0
47
0
3
Order By: Relevance
“…Not only limited to two dimensional but also three dimensional evaluations of palatal rugae using digital study models are found to be more useful and specific. 33 Advanced digital technique using Palatal Rugae Comparison Software to match the clinical photographs is used where the accuracy rate of identification is 99%, with a minimal error rate of 2%. 32 Many features of palatal rugae in our study were comparable to the studies done in different population but none of it matched accurately, which could be attributed to the variation in genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Not only limited to two dimensional but also three dimensional evaluations of palatal rugae using digital study models are found to be more useful and specific. 33 Advanced digital technique using Palatal Rugae Comparison Software to match the clinical photographs is used where the accuracy rate of identification is 99%, with a minimal error rate of 2%. 32 Many features of palatal rugae in our study were comparable to the studies done in different population but none of it matched accurately, which could be attributed to the variation in genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different digital model conversion techniques have shown no statistically mean differences when using 3D palatal rugae landmarks for comparison. 3D digital models are also proven as an effective tool in evaluating palatal rugae patterns for human verification and identification [13].…”
Section: Value Of Digital Modelsmentioning
confidence: 99%
“…It should be noted that, despite the current literature shows the existence of advanced technologies such as three-dimensional (3D) records of palatal roughness 18 , microscopic analysis of incremental lines of dental cement 19 and the use of softwares for morphometric measurements of dental pulps 20 , and a careful forensic dental examination associated with previous data in dental records, are sufficient to contemplate, with precision and rapidity, the success of the identification procedures, without need of further tests for human identification 13 .…”
Section: Resultsmentioning
confidence: 99%